The Potential Distribution and Maternal Lineage of Two Cetaceans Species (Grampus griseus and Pseudorca crassidens) in the Subfamily Globicephalinae from the Thai Andaman Sea and the Gulf of Thailand - Promporn Piboon; Anocha Poommouang; Kittisak Buddhachat; Jatupol Kampuansai; Siriwadee Chomdej; Patcharaporn Kaewmong; Kongkiat Kittiwattanawong; Korakot Nganvongpanit (Diversity, 2022)
Although the existence of two cetacean species in and around Thai Seas from within the subfamily Globicephalinae, Risso’s dolphin Grampus griseus G. Cuvier, 1812, and false killer whale Pseudorca crassidens Owen, 1846, has been known for decades, current knowledge on the abundance, genetic diversity, and conservation status of these marine mammals is limited as these are rare oceanic species for Thailand’s territorial waters. Frozen skin tissue samples taken from six cetaceans (four Risso’s dolphins: two false killer whales) stranded along Thai coastlines were investigated. We aimed to identify the maternal lineage and connection of our samples throughout their distribution range. Accordingly, we analyzed the dataset of 110 and 50 mtDNA control region sequences of Risso’s dolphins and false killer whales, respectively. This dataset was retrieved from the online database of the National Center for Biotechnology Information (NCBI) and included six mtDNA sequences obtained from Thai Seas. Two unique haplotypes of Risso’s dolphins were found in the Thai Andaman Sea, whereas one haplotype identified as being from the Gulf of Thailand is a common haplotype shared with other regions of the Pacific Ocean. Two haplotypes were found for false killer whales from the Thai Andaman Sea, and these were also in common with other regions of the Indo Pacific Ocean. While shared haplotypes with other regions may imply inheritance from the same female ancestor, we speculate that distinct populations with unique genetic structures also exist in Thai Seas. Beneficially, our results could be used to monitor alterations of haplotypes or to assess the maternal genetic diversity of designated species in the future to establish baseline information for Thai Seas and adjacent waters.